What does knowledge look like? Interpreting diagrams as contemporary hieroglyphics. (November 2019) - Bowen, Tracey; Evans, M Max
A significant challenge in interpreting and analyzing graphic representations is to understand the many reference points a graphically depicted object may have across its producer's personal and cultural experiences. An individual's exposure to socially constructed representations drives his or her propensity to use specific shared graphic objects, especially when attempting to articulate complex or abstract concepts. This multidisciplinary research study focuses on interpreting graphic representation types and analyzing the graphic objects individuals use to depict the abstract concept of knowledge. A sample of 833 individuals aged 5–65 participated in the study by constructing a drawing to answer the question, 'What does knowledge look like?'. Engelhardt's Language of Graphics (2002) graphic representation taxonomy was used to identify grouping and linking diagrams in the drawings. Next, graphic objects were coded and categorized within the drawings to identify the common representations, shared symbols, and non-depictive elements used to group and link. Using drawings fitting Engelhardt's grouping and linking graphic representation types, and Tversky's theories for constructing meaning through diagrams, this article examines how study participants combine and arrange common graphic objects to depict the concept of 'knowledge'. The results illustrate that individuals organize and arrange common graphic objects into groupings to communicate taxonomies or hierarchies based on spatial proximity; or connect and link them together using glyphs (e.g. arrows, dotted or straight lines) to communicate causal relationships. The findings also demonstrate how individuals employ common socially constructed graphic representations (or objects) as a visual communication tool and, through the exercise of drawing, as a tool for meaning or sense making. The graphic objects possess a shared meaning that the participants have seen circulating within their culture. The common ground that emerges from sharing graphic objects suggests a form of contemporary hieroglyphics that communicates meaning both inside and outside the community.